Perlindungan Hukum Dan Penanganan Buruh Migran Yang Bermasalah Di Luar Negeri - Rina Shahriyani Shahrullah; Grace Efride Kusa (Journal of Judicial Review, 2014)
When viewed from the side of quantity, the government program for placing Indonesian workers abroad can be said to work well, the number of Indonesian workers who work abroad are likely to continue to rise, but when viewed from the aspect of protection of migrant workers, especially legal protection, programs The government is still questionable in view of the vulnerability of the legal protection of migrant workers, especially migrant workers informally.As a comparative study in order to improve legal protection for Indonesian migrant workers, it is necessary to see a handling model that migrant workers can be quite successful, namely the handling of migrant workers Philippines.Indonesia regulations currently only limited regulation ministerial level, whereas the issue of Indonesian migrant workers affairs intersect with cross-departmental and cross-country. Filipino migrant workers setting stipulated in a law that specifically regulates the protection of migrant workers, namely the Republic Act 10022 (The Migrant Workers and Filipinos Act of 1995).Based on this research, it obtained information that the ratification of the International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families (Migrant Workers Convention 1990) both in Indonesia and the Philippines, both countries have a goal to protect and deal with migrant workers who work abroad. In this study, it was found that the legal protection of migrant workers and handlers Philippines better than the Indonesian. Therefore, this study recommends to legal protection and handling of migrant workers, Indonesia needs to learn from the Philippines.